Historical roots of extremist and radical Islamist thinking - Ushama, Thameem (IIUM Press, International islamic University Malaysia, 2017)
This study analyses the historical evolution of contemporary Muslimcontroversies over the historical roots of extremism by applying qualitativecontent analysis to relevant Qur’ānic verses, prophetic traditions and offeringsfrom early schools of Islamic thought. The study begins by defi ning Arabicterm ghulūw with regard to religious extremism and then briefl y introducesmanifestations of the phenomenon from the days of Prophet Nūḥ (A.S.) toJewish and Christian enthusiasts. The paper discusses impacts of extremistthinking on early Muslims with a focus on Kharijite and Muᶜtazilite schoolsand other related sects. In addition, a discussion of the misuse of certain termsand related legal rulings addresses fi ve matters of importance: [1] matterssignifi ed by specifi c appellations, errant legal rulings and consequences; [2]extremist doctrines; [3] extremist religious discourses; [4] rebuttal of errantdoctrines; and [5] implications of extremist designations and rulings.